Georgian men’s dress of XVII century : According to a comparative analysis of the paintings of the Italian missionary Cristoforo de Castelli and Georgian fine arts’ sources - Ugrekhelidze, Irina (Linguistics and Culture Review, 2021)
The article raises the issue of the importance of the work of Cristoforo de Castelli, an Italian missionary, Patrice of the Order of Theatine, in the study of Georgian historical costume. The sketches made by the author during his work in Georgia are analyzed, according to which it is possible to identify the types of clothes. According to the drawings, the clothes of different strata of the population are compared with the clothes of historical figures depicted in the monumental paintings of Georgian monuments of the same period and the clothes of the characters depicted in the illustrations of literary works. It emphasizes the identity of the costume depicted in Castelli's paintings and the miniatures of Georgian artist Mamuka Tavakarashvili and the similarity of some of the paintings. Finally, it is concluded that the visual material created over the years by Castelli as an eyewitness is still relevant today.